Taá¹bÄ«q NamÅ«zaj at-TaÊ¿lÄ«m bi al-TakhmÄ«n li IstÄ«Ê¿Äb al-MufradÄt al-Lugah al-Ê¿Arabiyyah laday TalamÄ«Å¼ Rauá¸ah al-Aá¹fÄl â€œNÅ«rul Husnayainâ€ bi Bukittinggi - Sari, Indah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This research is about applying the guessing teaching model to comprehend the vocabulary of the Kindergarten pupils